Comparison of the Use of Linkage in Cluster Integration With Path Analysis Approach - Fernandes, Adji Achmad Rinaldo; Solimun, Solimun (Frontiers in Applied Mathematics and Statistics, 2022)
This study aims to compare integrated clusters on various linkages (Ward, Complete, and Average linkage) with path analysis to classify the behavior of subservient to pay for mortgages. The data used are primary data from questionnaires filled out by Bank X customers, using purposive sampling. The measurement method used is the average score method. The results showed that cluster integration in the Ward linkage method with path analysis was the best method, by comparing the coefficient of determination. The variables of attitude, subjective norms, behavioral control, and intention to comply with paying explained the behavior of Bank X customers to comply with paying mortgages by 88.32%, while the remaining 11.68% was explained by variables outside the model.